Cardiovascular Risk of Concomitant Use of Atypical Antipsychotics and Stimulants Among Commercially Insured Youth in the United States - Zhang, Chengchen; Spence, O'Mareen; Reeves, Gloria; DosReis, Susan (Frontiers in Psychiatry, 2021)
Objectives To investigate the risk of cardiovascular events associated with concomitant use of stimulants and atypical antipsychotics (AAPs) among youth and evaluate whether AAP dose and duration of concomitant use modifies the risk. Methods We used IQVIA PharMetrics® Plus data from 2006 to 2015 to construct a retrospective cohort of commercially-insured youth aged 5-17 years old who initiated a stimulant medication. Time-varying concomitant stimulant/AAP use was defined as current, past and no concomitant use based on person months. The primary time-varying Cox proportional hazard regression analysis evaluated the risk of cardiovascular events comparing current concomitant use with past and no concomitant use, adjusted for baseline cardiovascular risk. A secondary analysis assessed the risk of cardiovascular events comparing AAP daily doses (<1 mg, 1-2 mg, >2 mg) and duration (<3months, 3-6months, >6months) of current concomitant use to no concomitant use. Cardiovascular outcomes included severe (i.e. stroke, acute myocardial infarction, ischemic heart disease) and less severe (i.e. angina pectoris, cardiac dysrhythmias, transient cerebral ischemia, hypertensive disease, tachycardia, palpitations, syncope). Results For this cohort of 61,438 youths, the incidence rate of severe cardiovascular events was 0.18 per 10,000 person-months, and all events occurred in no concomitant use months. The risk of less severe cardiovascular events was significantly higher in current concomitant users compared with no [HR:2.59 (95%CI: 1.72, 3.90)] and past [HR: 1.89 (95%CI: 1.10, 3.24)] concomitant users. Compared to no concomitant use, the risk of less severe cardiovascular events was significantly higher at all AAP daily doses [HR: <1 mg: 2.82 (95%CI: 1.72, 4.61); 1-2 mg: 2.22 (95%CI: 1.16, 4.25); >2 mg: 2.65 (95%CI: 1.50, 4.71)]. The risk of less severe cardiovascular events significantly elevated for all duration of use and was higher for <3 months of concomitant use [HR: <3 months: 3.45 (95%CI: 2.17, 5.47) relative to 3-6 months: 2.60 (95%CI: 1.29, 5.25) or >6 months: 2.61 (95%CI: 1.59, 4.30)]. Conclusions Severe cardiovascular events are rare. Concomitant stimulant/AAP use elevates the risk of less severe cardiovascular events. Periodic heart rate or blood pressure monitoring for youth on stimulant/AAP treatment may be warranted.